Peering Deeper: Student Perspectives on School Well-being and Youth Engagement - Kontak, Julia C.; Caldwell, Hilary A. T.; Hancock Friesen, Camille; Kirk, Sara F. L. (The Canadian Journal of Action Research, 2024)
We examined students’ perspectives on well-being and youth engagement in schools using a Youth Participatory Action Research approach. Students (N = 11) trained as peer researchers and then interviewed their peers. Interviews (N = 21) were analyzed using reflexive thematic analysis and six themes were developed: desire for versus reality of a healthy school, insufficient school strategies to promote well-being and mitigate harm, listening to and actioning students’ ideas, diverse opportunities for student engagement, pre-conceived ideas of student capability, and importance of a support role. Through this project, we peered deeper into students’ viewpoints about well-being and youth engagement in their schools.